Women's Social Readiness in Indonesia's National Economic Heroes Program (PENA): A Feminist Social Work Perspective from Special Region of Yogyakarta, Indonesia - Bambang Rustanto; Dyah Asri Gita Pratiwi; Eri Susanto; Tuti Kartika; Ayi Haryani; Aryohaji Istyawan (Women, Education, and Social Welfare, 2026)
This study examines the social readiness of women beneficiaries transitioning from conditional cash assistance under the Family Hope Program (PKH) to productive entrepreneurship through the Indonesian Archipelago Economic Heroes Program (PENA) in the Special Region of Yogyakarta. Employing a qualitative phenomenological approach, the study involved ten women beneficiaries selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and document analysis and were analyzed using Miles, Huberman, and Saldaña’s interactive model and Creswell’s horizonalization technique. The findings reveal that social readiness is ambivalent and manifested across four interconnected dimensions: emotive-attitudinal, cognitive, behavioral, and aspirational readiness. Social accompaniment helped transform transitional anxiety into achievement motivation, although cognitive readiness remained limited by low micro-financial literacy. Women demonstrated strong work resilience, but their behavioral readiness was constrained by the double burden and unequal distribution of domestic labor. The beneficiaries also expressed a need for continued technical assistance and more accessible financing. Feminist social work analysis confirms that these limitations are shaped more by time poverty and patriarchal inequalities than by individual shortcomings.